Compartimentação geomorfológica e processos deposicionais no megaleque fluvial do rio São Lourenço, Pantanal mato-grossense - Corradini, Fabrício Anibal [UNESP]; Assine, Mario Luis [UNESP] (My University, 2012)
The Pantanal wetland is an extensive depositional tract characterized by the presence of fluvial megafans, from which that of the Taquari River is the most extensive and well known. Located on the northern border of the Pantanal, the São Lourenço megafan is a large distributary fluvial system with an area of 16,000 km2, but poorly known regarding its geomorphological and geological features. The Sao Lourenço and the Taquari are coalescent megafans, having the Piquiri interfan meander river in between them. Based on the interpretation of satellite images and field validation, it was possible to identify channel patterns, to interpret depositional and erosional processes, to recognize the phenomena of river avulsion and to map depositional lobes. Three geomorphological zones were recognized on the São Lourenço megafan: 1) abandoned depositional lobes located in the upper/intermediate fan, composed of Pleistocene fluvial deposits and exhibiting distributary paleochannels on their surfaces, which are currently being dissected by tributary channels; 2) an active Holocene confined meander belt formed by fluvial aggradation in a N65E incised-valley; 3) active depositional lobes placed on the distal part of the system, which are the main site of sedimentation and are characterized by frequent avulsion events, channel bifurcation, distributary drainage pattern and the presence of depositional lobated landforms. The active depositional lobes were formed due to an important event of river avulsion that caused the lower portion of the meander belt to be abandoned.
Geomorphological zonation and depositional processes on the São Lourenço fluvial megafan, Pantanal wetland, Brazil
Keywords: Depositional processes; Fluvial megafan; Geomorphological zonation; Pantanal wetland; São Lourenço River